Effect of different sweeteners on the quality, fatty acid and volatile flavor compounds of braised pork - He, Zhi-gui; Zhang, Ying; Yang, Ming-duo; Zhang, Yu-qing; Cui, Ying-ying; Du, Mi-ying; Zhao, Dong; Sun, Hui (Frontiers in Nutrition, 2022)
This study aimed to evaluate the effect of different sweeteners (white sugar, Siraitia grosvenorii fruit, mogrosides, stevia glycoside) on the quality, fatty acid, and flavor of braised pork. The results showed differences between braised meat with other sweeteners and traditional braised pork. The traditional braised pork with white granulated sugar had a tremendous cooking loss and low water content when stewed for 60 min. The TBARS value increased by 14.39%, significantly higher than that in the group with Siraitia grosvenorii, mogroside and stevia glycoside (P <0.05). The cooking loss rate of the sample in the group added mogroside was small. The lean beef has the maximum L* value after 40 minutes of stewing, while the 60-minute stew sample is beautifully coloured and stretchable. Mogroside is thermally stable, may inhibit protein and lipid oxidation, and decreases cooking loss during stewing. The addition of Siraitia grosvenorii and stevia glycosides can also inhibit the aggravation of oxidation during stewing. The addition of Siraitia grosvenorii has a more significant inhibitory effect on lipid oxidation, and stevia glycosides have more advantages in improving meat color. The fatty acids of braised meat decreased with the increase of heating time, the UFA of the SF and mg group decreased slightly, the UFA: SFA ratio was greater than that of the WS group, and the SFA content of braised meat in Stevia glycoside group was higher than that of WS group. GC-IMS detected a total of 75 volatile flavor components in braised meat. The addition of sweetener increased the alcohols, esters and acids of braised meat. With the extension of stewing time, aldehydes and esters increased, and ketones decreased. After being cooked, the pork developed antioxidant peptides with exceptional nutritional value. Some proteins with color protection and antioxidant properties primarily exist in braised meat added with mogroside and stevia glycoside. This study can provide new insights into improving braised pork quality and the application of natural sweeteners.